PENGEMBANGAN MEDIA ISPRING SUITE 9 DALAM MENINGKATKAN PENGETAHUAN ANEMIA REMAJA PUTRI DI SMA NEGERI 11 MEDAN - Sinambela, Mentari; Firmansyah, Hardi; Emilia, Esi; Sandy, Yatty Destani (Jurnal Andaliman: Jurnal Gizi Pangan, Klinik dan Masyarakat, 2023)
It is estimated that around 1/3 of the world's population suffers from anemia, therefore it is appropriate that education regarding anemia be provided by utilizing technology such as media.ispiring suite 9 which can be used as a new educational medium to provide knowledge about anemia. This research aims to: (1) Produce mediaispring suite 9; (2) Know the qualifications of the mediaispring Suite 9 about anemia with the help of media experts, material experts and instrument experts; (3) Knowing the level of knowledge of young women after using mediaispring suite 9. The sampling technique is carried out usingproportional sampling, with a total sample of 68 grade 11 female students at SMAN 11 Medan. The research design in making media isResearch and Development model ADDIE (Analysis, Design, Development, Implementation, Evaluation). The research design uses a one group pretest-posttest design. Knowledge data collection techniques use quizizz-based tests, material experts, media experts, and test experts. Based on the research results, the average media feasibility value according to media experts in the first stage was 74.5%, including the feasible category, and the value in the second stage was 95.5% in the very feasible category. The average value of material feasibility according to material experts in the first stage was 73% in the feasible category and the score in the second stage was 94.5% in the very feasible category. The pretest and posttest scores to measure the increase in knowledge resulted in a gain score of 0.72 in the high category. So it can be concluded that the Ispring Suite media can be used by students in learning about anemia in young women.Keywords : Anemia, Ispring Suite 9 Media, ADDIE Model, Knowledge